Assessing heat tolerance in potatoes: Responses to stressful Texas field locations and controlled contrasting greenhouse conditions - Gautam, Sanjeev; Scheuring, Douglas C.; Koym, Jeffrey W.; Vales, M. Isabel (Frontiers in Plant Science, 2024)
In recent years, heat stress has affected potato production more frequently, resulting in lower marketable yields and reduced tuber quality. In order to develop heat-tolerant potatoes, it is necessary to select under heat-stress conditions and consider traits affected by heat stress. The Texas A&M Potato Breeding Program has selected potatoes under high-temperature stress for several decades. Ten potato cultivars, representing heat tolerant and sensitive clones based on past performance in Texas, were included in field trials for three years at the two main locations used by the Texas Breeding Program (Dalhart and Springlake, TX) to assess if the Texas field locations are suitable for heat tolerance screening. Both locations were confirmed as appropriate for heat stress screening. However, Springlake was a more stressful location since it had significantly lower yields of marketable tubers and increased percentages of tuber defects. Planting time did not have a significant effect at the most stressful location. The same ten potato clones were included in greenhouse experiments with contrasting temperatures (normal versus heat stress). There was confirmation that heat stress conditions resulted in significantly lower marketable yields, specific gravity, dormancy, and significantly higher percentages of tuber defects; however, significant differences existed between potato clones. Under heat stress conditions, Russet Burbank had a high percent of tubers with external defects, whereas Atlantic showed the highest percentage of internal defects (mainly internal heat necrosis). Vanguard Russet produced the highest marketable yield while maintaining a low percentage of external and internal defects. Russet Burbank and Atlantic were heat-sensitive controls for external and internal tuber defects, respectively. In contrast, Vanguard Russet can be used as a reliable heat-tolerant control. Including appropriate controls in heat stress studies will help identify clones with heat tolerance.